Barriers and facilitators to implementing stepped psychological care for people with aphasia: Perspectives of stroke health professionals. Issue 8 (17th November 2021) - Baker, Caroline; Rose, Miranda L.; Ryan, Brooke; Worrall, Linda
ABSTRACT: Background Concomitant aphasia and depression after stroke is highly prevalent, but there is a lack of psychological care in stroke rehabilitation for people with aphasia and family members. Evidence-based frameworks such as stepped psychological care may be viable, but the barriers and facilitators to translating this framework into aphasia rehabilitation practice are unknown. Aim The aim of this study was to identify, from the perspective of stroke health professionals, the barriers and facilitators to implementing stepped psychological care for depression after post-stroke aphasia. Method Five semi-structured focus groups of stroke health professionals were conducted ( n = 39) across the stroke care continuum. Verbatim transcripts were analyzed using Interpretive Description. Results Barriers and facilitators were identified within three core themes: knowledge, skills, and attitudes have the most impact on implementing stepped psychological care; the physical environment impacts on managing depression and communication disability for people with aphasia; and the support and leadership of the health organization influence change in any implementation of a stepped psychological care approach. Barriers included: no experience with stepped psychological care; limited understanding of aphasia and communication support; lack of adequate physical space and resources; lack of psychologists. Facilitators included: specialist training; enhancement of physical spaces; communication tools; leadership; funding; specialized staff. Conclusion Addressing the identified barriers and facilitators to stepped psychological care will improve the viability of implementing this evidence-based framework after post-stroke aphasia. Change may be driven through specialist training for health professionals in communication support; mood assessment and treatments; modification of physical space; and accessible resources.